PERSEPSI PEMILIK HOMESTAY DI KOTA DENPASAR TERHADAP PENGETAHUAN AKUNTANSI - Dirga Surya; Made , Edy Septian Santosa (KRISNA: Kumpulan Riset Akuntansi, 2024)
Business owners must recognize the importance of accounting in financial management and preparation of financial reports, thus understanding the owners' perceptions of their business and accounting is necessary. The objective of this research is to understand the perceptions of homestay owners in Denpasar regarding homestay businesses and financial accounting. This study utilized a descriptive analysis method, gathering data from 45 homestay owners in Denpasar. Validity and reliability tests indicated that all research instruments were valid and reliable. The research findings revealed that homestay owners have a very positive perception of homestay businesses, with a good understanding of homestay definitions and economic value. However, challenges related to business funding still exist. Additionally, homestay owners recognize the importance of bookkeeping and accounting, but limitations in knowledge and resources hinder their implementation. As a result, the quality of homestay financial reports still falls short of applicable accounting standards.